Probing the evidence: Can we bridge the theory-practice gap in language research? Book Review - Paquet, Pierre-Luc (Emerging Trends in Education, 2019)
This manuscript reviews Sato and Loewen (Eds.) book "Evidence-Based Second Language Pedagogy: A Collection of Instructed Second Language Acquisition Studies" which aim to provide researchers and L2 teachers with empirical evidence which can inform both SLA theories and L2 teaching.